EXPLORATION STUDY COMPARING THE EFFECTIVENESS OF METHOD OF TALKS WITH TEAM-BASED LEARNING METHOD - Sumiati, Sumiati (Vidya Karya, 2017)
Abstract- The review was affected by fundamental issues about how to best convey the learning material of Sociology. Team-Based Learning is accepted as a method of learning that can develop critical thinking skills. Team-Based Learning emphasizes opportunities for students to develop the ability to cooperate because it gives greater weight to the discussion (peer discussion) compared to learning by lecture method. This study aimed to determine whether a lecture or Team Based Learning teaches the content material better, develops skills, such as critical thinking; and creates a learning environment that is fun in learning Sociology. Data collection techniques in this study were conducted thorugh the study of literature from books and the results of previous research. The results of this study concluded that Team Based Learning method can improve oral communication and critical thinking skills, and create a more pleasant learning environment than lecture method.Â Keywords: Effectiveness, Team-based learning, SociologyÂ Abstrak. Kajian ini dipengaruhi oleh isu mendasar tentang bagaimana cara terbaik dalam menyampaikan materi pembelajaran Sosiologi. Team-Based Learning diterima sebagai metode pembelajaran yang dapat mengembangkan kemampuan berpikir kritis. Team-Based Learning menekankan pada kesempatan bagi siswa untuk mengembangkan kemampuan bekerja sama karena memberi bobot lebih besar pada kegiatan diskusi (peer discussion) dibandingkan pembelajaran dengan metode ceramah. Penelitian ini bertujuan untuk mengetahui dari dua metode yaitu ceramah atau Team Based Learning, metode mana yang lebih baik dalam mengajarkan materi, mengembangkan keterampilan, seperti berpikir kritis; dan menciptakan lingkungan belajar yang menyenangkan dalam belajar Sosiologi. Teknik pengumpulan data dalam penelitian ini dilakukan melalui studi literatur hasil-hasil penelitian terdahulu. Hasil penelitian menyimpulkan bahwa metode Team Based Learning dapat meningkatkan komunikasi lisan dan kemampuan berpikir kritis, serta menciptakan lingkungan belajar yang lebih menyenangkan daripada metode ceramah. Â Kata Kunci: keefektifan, pembelajaran berbasis kelompok, sosiologi